Effectiveness and Transmission of the ECB's Balance Sheet Policies - Jef Boeckx; Maarten Dossche; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2014)
We estimate the effects of exogenous innovations to the balance sheet of the ECB since the start of the financial crisis within a structural VAR framework. An expansionary balance sheet shock stimulates bank lending, stabilizes financial markets, and has a positive impact on economic activity and prices. The effects on bank lending and output are smaller in the member countries that have been more affected by the financial crisis, in particular those countries where the banking system is less well-capitalized.
Keywords: C32; E30; E44; E51; E52; 330; unconventional monetary policy; ECB balance sheet; euro area; VAR